(untitled) (Journal of the Bangladesh Agricultural University, 2011)
Effects of neem, betel leaf, devil’s tree, jute and turmeric against natural gastrointestinal nematodes in sheep and on some hematological parameters (TEC, Hb and PCV) and body weight were studied. Thirty (30) naturally parasitized sheep were randomly divided into six groups(A, B, C, D, E and F), each consisting of five sheep. Ten percent water extract of leaves of neem, betel leaf, devil’s tree and jute were administered orally to the sheep of group A, B, C and D, respectively. Sheep of group E was treated orally with 10% water extract of rhizome of turmeric. Sheep of group F was kept as infected control group. Fecal samples, hematological parameters and body weight were examined before treatment and on 7th, 14th, 21st and 28th day. A significant (p<0.01) reduction of EPG count was found following administration of neem (37.60-47.03%), betel leaf (6.43-14.00%), devil’s tree (3.04-11.04%), jute (0.50-5.26%) and turmeric (0.46-8.30) in sheep. The EPG count of the control group (F) were significantly (p<0.01) increased up to the last day of experimental period. After treatment with neem, betel leaf, devil’s tree, jute and turmeric total erythrocyte count (TEC), hemoglobin (Hb) content and packed cell volume (PCV) were increased significantly (p<0.01 and p<0.05) in sheep. The body weight was increased significantly (p<0.01 and p<0.05) in neem, betel leaf, devil’s tree, jute and turmeric treated sheep. On the other hand, body weight was decreased in untreated control group. The present study reveal that 10% water extract of neem was moderately effective and betel leaf, devil’s tree, jute and turmeric were relatively less effective against gastrointestinal nematodes in sheep. Keywords: Neem; Betel leaf; Devil’s tree; Jute; Turmeric; Gastrointestinal nematode DOI: 10.3329/jbau.v8i2.7935 J. Bangladesh Agril. Univ. 8(2): 259-263, 2010